2015
DOI: 10.1248/cpb.c15-00469
|View full text |Cite
|
Sign up to set email alerts
|

Clean Synthesis of <i>N</i>-Pyrrolyl Azoles by Metal-Free Oxidative Cross-Coupling Using Recyclable Hypervalent Iodine Reagent

Abstract: The facile and clean oxidative coupling reaction of pyrroles with azoles has been achieved using the recyclable hypervalent iodine(III) reagents having adamantane structures. These iodine(III) reagents could be recovered from the reaction mixtures by a simple solid-liquid separation, i.e., filtration, for reuse.Key words oxidative coupling; hypervalent iodine reagent; recycle; pyrrole; azole; C-N bond formationThe N-pyrrolyl azoles are important fragments in the molecules of biological systems or in many pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 58 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…As a result, when TMSBr was used in combination with PIDA, the best results were obtained in forming N-pyrrolylazole, and the C-N-coupling reaction proceeded in good yield. 107,108) The scope of the substrate for our method proceeded without being affected by the N-substituent, and products 5 were obtained in good yield (Chart 13). N-Free pyrrole and 2-ethyl Chart 16.…”
Section: Cross-coupling Reaction Of Pyrrolesmentioning
confidence: 99%
“…As a result, when TMSBr was used in combination with PIDA, the best results were obtained in forming N-pyrrolylazole, and the C-N-coupling reaction proceeded in good yield. 107,108) The scope of the substrate for our method proceeded without being affected by the N-substituent, and products 5 were obtained in good yield (Chart 13). N-Free pyrrole and 2-ethyl Chart 16.…”
Section: Cross-coupling Reaction Of Pyrrolesmentioning
confidence: 99%
“…Catalysts 61 and 73 can be readily separated from reaction mixtures by filtration and reused several times without any significant loss in catalytic activity. 52 In 2018, Wei et al developed inorganic ligand-coordinated polyoxametallate (POM) iodine catalyst 76 by treating ammonium heptamolybdate (75) with orthoperiodic acid (74) in an aqueous medium at 95 °C for 3 hours (Scheme 14). 53 This catalyst selectively oxidizes various alcohols, including primary, secondary, allylic, and benzylic, under aerobic conditions without the use of toxic oxidants such as Oxone ® , or sensitive organic ligands.…”
Section: Scheme 13 Oxidation Of 5-cholestan-3-ol 71 With 61mentioning
confidence: 99%
“…73 In 2015, Kita and co-workers achieved the cross-coupling of pyrroles 128 and azoles 129 to afford coupling product 130 in 52-78% yield using 1,3,5,7-tetrakis [4-(diacetoxyiodo)phenyl]adamantane (80) in combination with bromotrimethylsilane at 70 °C (Scheme 21). 74 In 2018, Kita et al reported the cross-coupling reaction of pyrroles 131 with the electron-rich arene 132 using adamantane-core-based reagent 80 in hexafluoroisopropanol (HFIP) at room temperature (Scheme 22). 75 Scheme 22 Metal-free oxidative cross-coupling of pyrroles 131 with 132 using reagent 80…”
Section: Review Synthesismentioning
confidence: 99%
“…Utilizing the reaction of N-methylpyrrole 3b, the C2-arylation developed in this study first gave coupling product 5b in 61% yield. Subsequently, under the conditions we have previously developed, 12 the second N-arylation introduced the 1,2,3-triazole 6a and 1,2,3-benzotriazole 6b moieties took place and the diarylated products 7a and 7b were obtained (Scheme 3). Nitrogen heterocycles are known as core of various natural products and functional materials, among which azoles and pyrroles have the most frequent occurrence.…”
Section: Scheme 1 Cross-coupling Reaction Of Pyrroles Using Recyclabmentioning
confidence: 99%